Balancing, Bandwagoning or Hedging? Independent Ceylon's Reaction to Regional Hegemony. (September 2015) - De Silva, Shakthi
The foreign policy of Ceylon under the premiership of D.S. Senanayake maintained a distinct alignment with its former coloniser Great Britain. The zenith of this relationship was the defence agreement which came into effect upon independence in 1948. Utilising the existing scholarship on neorealism and the concept of security dilemma, analysis of the reasons behind this strategic alignment exposes the threat perception Ceylon faced from its regional hegemon, India. This study surveys such threat perceptions faced by the island at the time of independence and argues that this led to a balancing strategy with Britain. It first locates Ceylon's foreign policy employing the taxonomies of balancing, bandwagoning and hedging and then examines how Ceylon's extra-regional alignment with the UK enabled her to eschew from a security dilemma with India.